Aesthetics: Quantification and Deconstruction A Case Study in Motorcycles - Chandra, Sushil (Design Science and Innovation,, 2018)
This book addresses a perennial challenge for product planners and designers alike: how to objectively specify and quantify the aesthetics of products. It provides automotive product planners with a framework for the grammar of aesthetics and a tool for quantifying the aesthetics of an intended product. Further, it equips styling designers with a tool for connecting engineering and aesthetics. Given the author's extensive experience in motorcycle design, the motorcycle has been chosen as the frame of reference for automobiles. Specifically in the field of automobile design, where engineering and aesthetics go hand in hand, it also becomes important to clearly and objectively define the relationship between engineering design and aesthetics. Accordingly, this book (1) clearly establishes the objective parameters of aesthetics, (2) puts forward a method for quantifying aesthetics, (3) identifies the engineering design parameters affecting aesthetics, and (4) determines the relationship between parameters of aesthetics and engineering design. As such, it offers a useful guide not only for design professionals, but also for students and researchers of design.